Ceiling and roof construction - International Code Council ([Illinois] : International Code Council, 2006)
This video covers basic requirements for ceiling and roof construction including methods of construction, framing of openings, lateral support and cutting and notching
Host: Jim Powell
DVD format
Keywords: Ceilings; Roofs -- Design and construction